The Influence of Hyper Content-Based Practicum Guidance on Students' Scientific Literacy Ability in Material Structure and Function of Plant Tissues for Class XI IPA Students at SMA Negeri 2 Gowa - Sri Rahayu (Universitas of Muhammadiyah Makassar, 2021)
This research is an experimental researchQuasi Experimental Design which aims to determine the effect of a practicum-based guidehyper content on the scientific literacy skills of class XI IPA students at SMA Negeri 2 Gowa on the material structure and function of plant tissue with a research design